Drug repositioning : bringing new life to shelved assets and existing drugs - Barratt, Michael J.; Frail, Donald (Hoboken, N.J. : Wiley, 2012)
BThe how's and why's of successful drug repositioning /b/ Drug repositioning, also known as drug reprofiling or repurposing, has become an increasingly important part of the drug development process. This book examines the business, technical, scientific, and operational challenges and opportunities that drug repositioning offers. Readers will learn how to perform the latest experimental and computational methods that support drug repositioning, and detailed case studies throughout the book demonstrate how these methods fit within the context of a comprehensive drug repositioning strategy./ iDrug Repositioning/i is divided into three parts:/ ulli bPart 1, Drug Repositioning: Business Case, Strategies, and Operational Considerations, /b examines the medical and commercial drivers underpinning the quest to reposition existing drugs, guiding readers through the key strategic, technical, operational, and regulatory decisions needed for successful drug repositioning programs./ /lili bPart 2, Application of Technology Platforms to Uncover New Indications and Repurpose Existing Drugs, /b sets forth computational-based strategies, tools, and databases that have been designed for repositioning studies, screening approaches, including combinations of existing drugs, and a look at the development of chemically modified analogs of approved agents./ /lili bPart 3, Academic and Non-Profit Initiatives & the Role of Alliances in the Drug Repositioning Industry/b, explores current investigations for repositioning drugs to treat rare and neglected diseases, which are frequently overlooked by for-profit pharmaceutical companies due to their lack of commercial return./ /li/ul The book's appendix provides valuable resources for drug repositioning researchers, including information on drug repositioning and reformulation companies, databases, government resources and organizations, regulatory agencies, and drug repositioning initiatives from academia and non-profits./ With this book as their guide, students and pharmaceutical researchers can learn how to use drug repositioning techniques to extend the lifespan and applications of existing drugs as well as maximize the return on investment in drug research and development.
Drug repositioning : the business case and current strategies to repurpose shelved candidates and marketed drugs / John Arrowsmith and Richard Harrison -- Opportunities and challenges associated with developing additional indications for clinical development candidates and marketed drugs / Donald E. Frail and Michael J. Barratt -- Clinical and operational considerations in repositioning marketed drugs and drug candidates / Damian O'Connell, David J. Sequeira, and Maria L. Miller -- Regulatory considerations and strategies for drug repositioning / Ken Phelps -- Computational and bioinformatic strategies for drug repositioning / Richard Mazzarella and Craig Webb -- Mining scientific and clinical databases to identify novel uses for existing drugs / Christos Andronis [and others] -- Predicting the polypharmacology of drugs : identifying new uses through chemoinformatics, structural informatics, and molecular modeling-based approaches / Li Xie [and others] -- Systematic phenotypic screening for novel synergistic combinations: a new paradigm for repositioning existing drugs / Margaret S. Lee -- Phenotypic in vivo screening to identify new, unpredicted indications for existing drugs and drug candidates / Michael S. Saporito, Christopher A. Lipinski, and Andrew G. Reaume -- Old drugs yield new discoveries : examples from the prodrug, chiral switch and site-selective deuteration strategies / Adam J. Morgan [and others] -- Repurposing drugs for tropical diseases : case studies and open-source screening initiatives / Curtis R. Chong -- Drug repositioning efforts by nonprofit foundations -- Business development strategies in the repositioning industry / Aris Persidis and Elizabeth T. Stark -- A case study in drug repositioning : Sosei / Akinori Mochizuki and Makiko Aoyama.
Includes bibliographical references and index.
Print version record.
Keywords: Drug development; Pharmaceutical industry; Drug Repositioning; Computational Biology -- methods; Drug Industry -- economics; Pharmaceutical Preparations -- economics; Medical; MEDICAL -- Pharmacology; Drug development; Pharmaceutical industry; Electronic books; Electronic books